If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -396 = -9(8x + -12) Reorder the terms: -396 = -9(-12 + 8x) -396 = (-12 * -9 + 8x * -9) -396 = (108 + -72x) Solving -396 = 108 + -72x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '72x' to each side of the equation. -396 + 72x = 108 + -72x + 72x Combine like terms: -72x + 72x = 0 -396 + 72x = 108 + 0 -396 + 72x = 108 Add '396' to each side of the equation. -396 + 396 + 72x = 108 + 396 Combine like terms: -396 + 396 = 0 0 + 72x = 108 + 396 72x = 108 + 396 Combine like terms: 108 + 396 = 504 72x = 504 Divide each side by '72'. x = 7 Simplifying x = 7
| 6(2x-4)=3(4x-22) | | 4a+3=-9 | | p^2-10p-15=0 | | 3t-18=4t-16 | | 6x-2=70 | | -498=6(9x+16) | | 20=-3x+7(-2x+25) | | -7(x+8)-44=3-61 | | 8x^3-336x^2+2760x+1608= | | 2(7-3x)+1=2x-1 | | (3x+4)(x-3)=10 | | 8+-176=-72 | | 567=-6(10x-16) | | 8+176=-72 | | (x-8)*(x-8)-18=-2 | | 4k-7=2+k | | 504=-16x^2+484 | | 2(g-2)-4=3(g-3) | | 209-3x=33x+21 | | 75-6x=12x+15 | | 3+5d=11+4d | | 6x-7=3x-11 | | 9(2x+14)-4(3x+17)=64 | | -3x+6=18 | | 3x^2-27x=-2x^2-9x-16 | | 5.50+4.00(486-a)=2416 | | -486=6(7x-11) | | 7-8x=47-22x | | 3x-5=5x+12 | | 4(5y-4)=12y | | -61*3=x | | -120=-4(7x+9) |